PENGENDALIAN PENYAKIT BUSUK LUNAK UMBI KENTANG (Erwinia carotovora) DENGAN MEMANFAATKAN AGENS HAYATI Bacillus subtilis dan Pseudomonas fluorescens - Cokorda Javandira; Luqman Qurata Aini; Abdul Latief Abadi (Jurnal HPT (Hama Penyakit Tumbuhan), 2013)
Potato (Solanum tuberosum L.) is one of the commodities of potential as a sourceof carbohydrates and important on Indonesia's economy. One of the constraints ofpotato production is soft rot disease caused by Erwinia carotovora (syn.Pectobacterium carotovorum) which is needed to be controlled. One alternativecontrol measures is the used of bacteria Bacillus subtilis and Pseudomonasfluorescens for biological control. The purpose of this research is to know thepotential of B. subtilis and P. fluorescens in single and in combination to inhibitpotato soft rot diseases caused by E. carotovora. The results showed thatbiological control agents B. subtilis and P. fluorescens in single or in combinationboth of them (T3 to T17) have potential in inhibiting the growth of pathogenic E.carotovora by showing the clear zone. Biological agents provides nearly the sameeffect if compared with the bactericide Agrept (T2). Based on the results of thestatistical analysis, the treatment 11th and treatment 14th showed a clear zonewider than the Agrept treatment (T2). The treatment 11th contain combination ofbiological agents B. subtilis (109 cfu/ml) and P. fluorescens (105cfu/ml), while the treatment 14th contain combination of biological agents B.subtilis (107 cfu/ml) and P. fluorescens (105 cfu/ml).Keywords: Erwinia carotovora, Bacillus subtilis and Pseudomonas fluorescens